2005
DOI: 10.1007/s15010-005-4004-9
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Bordetella Infections in Patients with Acute Exacerbation of Chronic Bronchitis

Abstract: Background: Acute exacerbations of chronic bronchitis (AECB) are associated with a variety of viral and bacterial infectious agents, some of which are potentially preventable by immunization. Bordetella pertussis, which causes whooping cough, has not been studied in this context. We aimed to assess the role of Bordetella infections in patients with AECB. Patients and Methods: Patients with AECB, who presented to participating private practices in Basel, Switzerland, between October 2000 and June 2002, were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 34 publications
0
23
0
2
Order By: Relevance
“…Представители этого рода -патогены, вызывающие коклюш и инфекционный бронхит. От-мечается их роль в развитии обострений хронического бронхита [32].…”
unclassified
“…Представители этого рода -патогены, вызывающие коклюш и инфекционный бронхит. От-мечается их роль в развитии обострений хронического бронхита [32].…”
unclassified
“…While the association between COPD and pertussis in clinical settings has not been investigated extensively, some preliminary studies have shown, albeit in a non-definitive manner, an increase in the risk of pertussis in patients with COPD as compared to non-COPD patients. 32,33 In their pilot study, Bonhoeffer et al 32 assessed patients with acute exacerbations of chronic bronchitis (AECB) (N = 26) for a concomitant presence of Bordetella infection using nasopharyngeal swabs for culture, polymerase chain reaction, and blood samples for serology. The investigators discovered that eight of the patients (31%) were seropositive for Bordetella infections, five of them (19%) being confirmed by ELISA technique to be due to B. pertussis.…”
Section: Clinical Evidence On the Association Of Copd And Pertussismentioning
confidence: 99%
“…20 Elevated levels of the latter pathogen are more likely to be associated with severe COPD or when systemic steroids and/ or antibiotics had been prescribed in the preceding months 21. In addition, Bordetella pertussis , the re-emergent pathogen responsible for pertussis (whooping cough), has been associated with 31% of acute exacerbations of chronic bronchitis, according to one pilot study 22. While infections are the most common cause of exacerbations,1 the apparent increased susceptibility to this etiologic factor in patients with COPD is not well understood.…”
Section: Triggers and Effects Of Copd Exacerbationsmentioning
confidence: 99%